Changing Perspectives on the Facility Siting Process - Laws, David; Susskind, Lawrence (Maine Policy Review, 1991)
Building regionally necessary but locally noxious facilities such as power plants, landfills, waste incinerators and prisons has become increasingly difficult. David Laws and Lawrence Susskind discuss some of the traditional steps involved, including needs assessment, choice of technology, site selection, assessing and mitigating impacts, and management. They provide an alternative approach to facility siting that includes, among other things, seeking consensus, working to develop trust, setting realistic timetables, getting agreement that the status quo is unacceptable, choosing a design that best addresses the problem, and fully compensating for negative aspects of the facility.